The Implementation of the Verbal and Graphic Teaching Methods in Pedagogical Heritage of S. Shevchenko (Pedagogy of Higher and Secondary Education, 2014)
Моskalyova О. І. The Implementation of the Verbal and Graphic Teaching Methods in Pedagogical Heritage of S. Shevchenko.In the article there is analyzed and summarized the experience of the native pedagogue-innovator S. Shevchenko concerning the development of the theoretical bases and the implementation of the verbal and graphic teaching methods.There are investigated the positive sides if using the structural and logical schemes at the different level of the learning process, there is underlined the reasonability of their further implementation and the use in the educational and upbringing process of modern school.
Keywords: learning process; abstract-symbolic use of visual methods; verbal and graphic method; list of reference signals; pedagogue-innovator